Error Analysis of Class VIII Students in Understanding Mathematics Problems in the PISA Model at MTS Terpadu Nurul Hidayah Tangen for the 2020/2021 Academic Year - Astuti, Nanda Mudi; Hw, Slamet (Universitas Muhammadiyah Surakarta, 2021)
This study was conducted with the aim of knowing and describing the causes of students making mistakes in understanding the PISA model math problems on the Number Pattern material. This type of research is descriptive qualitative research.The subjects in this study were class VIII MTs Terpadu Nurul Hidayah Tangen students for the 2020/2021 academic year. Data collection techniques used in this study were tests, interviews, and documentation. The validity of the data using triangulation techniques.The data analysis technique was carried out in three stages, namely data reduction, data presentation, and data verification and conclusion drawing. The analytical framework was developed based on the Newman error category. The results showed that the number of errors made by students in understanding the PISA model questions was 23.29%.Factors causing these errors in general are due to the ability of students who cannot interpret the meaning of the questions properly, and the level of understanding and creativity of students is low in identifying problems.